Human trafficking across the Americas: Victims, services, and the law - Tom D. Kennedy; Brittany Plombon; Caroline Haskamp; Bianca Howard; Cammi Shoultz; Danielle Millen; David Detullio; Jennifer Davidtz (Child Protection and Practice, 2025)
Human trafficking has garnered increasing attention and global awareness as a significant violation of fundamental human rights. This modern-day slavery is actively occurring both internationally and in our local communities. The Trafficking in Persons (TIP) Report outlines the extent and typical services allocated for survivors of human trafficking by country. Additionally, the report details the funding allocated toward prevention and services, as well as the annual efforts of each country's government to meet the minimum standards outlined by the Trafficking Victims Protection Act (TVPA, 2000). This study aimed to examine the chronological growth and decline of specific government efforts to combat human trafficking in countries across North, South, and Central America. Specifically, descriptive differences in trends and services were explored country by country, comparing the narratives provided in 2014 to those offered in the 2018 TIP report. The overall trends indicate that almost two-thirds of the governments of countries in the Americas have remained relatively unchanged in their efforts to comply with the minimum standards of the TVPA (TIP, 2014; TIP, 2018). Only three countries have consistently remained in the top tier (i.e., Canada, the United States of America, and Chile).